Justine effect: punishment of the unduly self-sacrificing cooperative individuals - Kuběna, Aleš Antonín; Houdek, Petr; Lindová, Jitka; Příplatová, Lenka; Flegr, Jaroslav (PloS one, 2014)
BACKGROUND: Allowing players to punish their opponents in Public Goods Game sustains cooperation within a group and thus brings advantage to the cooperative individuals. However, the possibility of punishment of the co-players can result in antisocial punishment, the punishment of those players who contribute the most in the group. To better understand why antisocial punishment exists, it must be determined who are the anti-social punishers and who are their primary targets. METHODS: For resolving these questions we increased the number of players in a group from usual four to twelve. Each group played six rounds of the standard Public Goods Game and six rounds of the Public Goods Game with punishment. Each player in each round received 20 CZK ($ 1.25). Players (N = 118) were rematched after each round so that they would not take into consideration opponents' past behavior. RESULTS: The amount of the punishment received correlated negatively with the contribution (ρ = -0.665, p<0.001). However, this correlation was positive for players in the highest contributors-quartile (ρ = 0.254, p<0.001). Therefore, the graph of relation between the contribution given and punishment obtained was U-shaped (R2 = 0.678, p<0.001) with the inflection point near the left boarder of the upper quartile. The antisocial punishment was present in all groups, and in eight out of ten groups the Justine Effect (the positive correlation between the contribution to the public pool and the risk of suffering punishment in the subpopulation of altruistic players) emerged. In our sample, 22.5% subjects, all of them Free riders and low contributors, punished the altruistic players. CONCLUSIONS: The results of our experimental game-study revealed the existence of the Justine effect--the positive correlation between the contribution to the public pool by a subpopulation of the most altruistic players, and the amount of punishment these players obtained from free-riders.
Keywords: Punishment; kooperační chování; Cooperative Behavior; altruismus; teorie her; Humans; sociální spravedlnost; Altruism; Game Theory; lidé; trest; Social Justice